Society - Water - Technology: A Critical Appraisal of Major Water Engineering Projects - Hüttl, Reinhard F.; Bens, Oliver; Bismuth, Christine; Hoechstetter, Sebastian (Water Resources Development and Management, 2016)
Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Industry/Water Technologies; Environmental Economics; International Environmental Law